Communicating Photograph Content Through Tactile Images to People With Visual Impairments - Pakėnaitė, Karolina; Nedelev, Petar; Kamperou, Eirini; Proulx, Michael J.; Hall, Peter M. (Frontiers in Computer Science, 2022)
Millions of people with a visual impairment across the world are denied access to visual images. They are unable to enjoy the simple pleasures of viewing family photographs, those in textbooks or tourist brochures and the pictorial embellishment of news stories etc. We propose a simple, inexpensive but effective approach, to make content accessible via touch. We use state-of-the-art algorithms to automatically process an input photograph into a collage of icons, that depict the most important semantic aspects of a scene. This collage is then printed onto swell paper. Our experiments show that people can recognise content with an accuracy exceeding 70% and create plausible narratives to explain it. This means that people can understand image content via touch. Communicating scene foreground is a step forward, but there are many other steps needed to provide the visually impaired with the fullest possible access to visual content.